ANALISIS KOMPARATIF PENDAPATAN PETANI PADI YANG MENJUAL GABAH DAN BERAS DI DESA LEMBONTONARA KECAMATAN MORI UTARA KABUPATEN MOROWALI UTARA - Supratmini Supratmini; Alimuddin Laapo; Muh Fahrudin Nurdin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The purpose of this study was to determine income levels and income differences between farmers selling unhulled rice and rice, and to determine which marketing pattern was more suitable in Lembontonara village of Mori Utara sub district of Morowali Utara district. The Proportional Stratified Random Sampling technique was used to select 13 farmers selling unhulled rice and 24 farmers selling rice. The collected data was analyzed using income analysis, t-test and descriptive comparison. The analysis results showed that for each planting season the farmers selling unhulled rice generated revenue of IDR 17,939,385.00 ha-1 at a total cost of IDR 7,294,114.18 ha-1 whereas their counterparts generated revenue of IDR 24,466,485.19 ha-1 at a total cost of IDR10,988,290.03 ha-1. The income of the farmers selling rice (IDR 13,478,195.16 ha-1) was significantly higher than the farmers selling unhulled rice (IDR 10,645,270.82 ha-1). However, it is recommended that the farmer sale their product in the form of unhulled rice in Lembontonara village.